PENGARUH INKLUSI KEUANGAN SYARIAH TERHADAP PERTUMBUHAN USAHA MIKRO KECIL DAN MENENGAH DI BANK ACEH SYARIAH SUTOMO KCP KOTA MEDAN - Nancy Rahma Yuni; Ahmad Adib Nasution (MUTLAQAH: Jurnal Kajian Ekonomi Syariah, 2022)
This study aims to determine: 1). Knowing the effect of Islamic financial inclusion on the growth of micro, small and medium enterprises at Bank Aceh Syariah Sutomo KCP Medan City, and 2). Analyzing the efforts made in accelerating access to Islamic finance to encourage micro, small and medium enterprises to grow. This research is a survey research. The population in this study is the customer user of the Sharia Bank Sutomo KCP Medan City. The sampling technique used purposive sampling with a total sample of 10 people. The data collection technique uses a questionnaire that has been tested for validity and reliability.The data analysis technique used is simple regression. The results of this study indicate that: 1). Islamic financial inclusion has an effect on the growth of micro, small and medium enterprises mediated by Sharia Bank Sutomo KCP Medan City, the indirect effect significance.2). In this study, the data fulfills a normal distribution. The results show that Islamic financial inclusion has an influence on the growth of micro, small and medium enterprises.